Effect of calcium carbonate filler and alkali treatment on physical and elastic properties of jute mat reinforced polyester resin composites (Bangladesh Journal of Physics, 2020)
Polyester resin-jute mat reinforced composites with different wt% of calcium carbonate (CaCO3) filler were fabricated using a simple cold press molding method. The effects of CaCO3 filler and alkali (NaOH) treatment on various physical and elastic properties were evaluated. Water absorption (WA) increases with the increase of soaking time and load. The maximum WA was observed for 5 wt% addition of CaCO3 and for more CaCO3, WA decreases. The ultimate tensile strength (UTS) and flexural strength (FS) decreases with the addition of CaCO3 for 0.5 wt% NaOH treated composites but for 5 wt% NaOH treated composites UTS and FS increases with the addition of CaCO3 filler. The optimum filler addition is about 5 wt% CaCO3. With the addition of CaCO3, tangent modulus increases for 0.5 wt% NaOH treated composites and for 5 wt% NaOH treated composites it increases up to a maximum value and then decreases. The effect of load on tensile and flexural properties is also discussed.Bangladesh Journal of Physics, 26(2), 61-68, December 2019